The role of intraventricular antibiotic therapy in the treatment of ventriculo-peritoneal shunt infection in children - Sahin, Ayse; Dalgic, Nazan; Kilic, Mustafa; Kirgiz, Pinar; Kanik, M. Kemal; Oz, Ersoy; Yilmaz, Adem (SPRINGER, 2021)
Background In this study, the effectiveness of intraventricular (IVT) antibiotic administration was evaluated in the treatment of ventriculo-peritoneal (VP) shunt infection by comparing patients who received only systemic antibiotic treatment with patients who received antibiotics added to systemic therapy by IVT route. Methods From July 2009 to July 2019, 78 shunt infection episodes of 74 pediatric patients with bacterial growth in cerebrospinal fluid (CSF) culture who were treated with the diagnosis of VP shunt infection were retrospectively analyzed. The demographic data, clinical and laboratory parameters, antimicrobial management, and treatment outcomes of patients with VP shunt infections were recorded. Results Thirty-eight of 78 shunt episodes received only systemic antibiotic treatment, and 40 had received IV plus IVT treatment. The mean age of the entire patient group was 16.7 +/- 21.3 months (range, 1 to 95 months). There was no significant difference between the two treatment groups in terms of mean age. The most common microorganism grown in CSF culture was coagulase-negative Staphylococcus. However, in the group that received IV plus IVT treatment, gram-negative bacteria were predominant (42.1% versus 20%), and this group had carbapenem-resistant and ESBL positive gram-negative bacteria growth. In the duration of CSF sterilization, hospital stay was statistically significantly shorter in the group receiving IV plus IVT treatment (p=0.000, p=0.000, respectively). Conclusion Our study shows that IVT administration of antibiotics shortens the duration of CSF sterilization, duration of antibiotic use, and the duration of hospital stay. For the treatment of VP shunt infection, the usage of IVT treatment in a particular group of a pediatric age is promising. However, further efforts should be done for supporting the current results by randomized controlled studies.
Keywords: Intraventricular; Treatment; Children; Shunt infections; Neurosciences & Neurology; Pediatrics; Surgery